Social intelligence and pathological gaming: a longitudinal study of the associations among negative emotions, social intelligence, aggression, and pathological gaming in adolescents - Lee, Sung Je; Jeong, Eui Jun; Choi, Jae In; Park, Man Su (Frontiers in Psychiatry, 2024)
Introduction Pathological gaming continues to be highlighted as one of the most critical issues concerning adolescents. Numerous studies have aimed to elucidate the relationships between adolescents' negative emotions (e.g., peer stress, anxiety, loneliness) and social factors (e.g., social skills and relationships) with pathological gaming. Despite the recognition of social intelligence as a crucial factor related to social factors in adolescents, there is a paucity of research examining pathological gaming and social intelligence through longitudinal analyses. Method This study focuses on exploring the factors that induce or inhibit pathological gaming among adolescents by analysing three-year longitudinal data from Korean adolescent gamers (N=968). Using a structural equation model, the study examines the relationships between adolescents' negative emotions (e.g., peer stress, anxiety, loneliness), social intelligence, and pathological gaming to elucidate their associations. Results The results indicate that negative emotions can potentially reduce levels of social intelligence and increase aggression. Increased aggression, in turn, appears to be associated with higher levels of pathological gaming. Social intelligence was found to impact pathological gaming potentially negatively and may exert a significantly stronger influence on aggression compared to negative emotions. Discussion The study's findings suggest that bolstering adolescents' social aptitude and addressing mental health concerns could serve as beneficial interventions in tackling issues associated with excessive media engagement among youth. These findings suggest that, within the context of adolescent pathological gaming, social intelligence could significantly affect aggression and emerge as a key variable that may lead to pathological gaming.